Analysis of Internal Control Systems for Merchandise Inventory in Minimizing Damage and Loss of Merchandise at the Indomaret Minimarket in Surabaya, Bengkulu City - Prasetya, Andika Dwi Yudha; Susanti, Neri; Noviantoro, Rinto (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
Accounting Information System. The formulation of the problem in this study is how the internal control system for merchandise inventory minimizes damage and loss of merchandise at the Indomaret Minimarket Surabaya Bengkulu City. The purpose of this study was to determine the internal control system for merchandise inventory at the Indomaret Minimarket Surabaya Bengkulu City. This type of research is descriptive research. The research method used is descriptive qualitative method. Data collection was carried out by means of interviews and documentation. Sources of data used primary data and secondary data. The results of this study are that the internal control system for merchandise inventory at the Indomaret Minimarket Surabaya Bengkulu City has not been implemented properly because there is still no warehouse function. Effective measures to minimize damage and loss of merchandise and maintain inventory levels have not been implemented properly.